Arms sales and child health - Imti Choonara; Andrew Feinstein (BMJ Paediatrics Open)
The adverse effects of armed conflict on child health are well recognised. The relationships among the arms trade, armed conflict and child health are less clearly defined. The arms trade is one of the largest industries in the world (total expenditure US$1917 billion in 2019), generating colossal profits to private companies and individuals at the expense of taxpayers throughout the world. The money wasted on weapons designed to kill and maim should be used for more socially useful products, such as clean water, food, health and education. The sustainable development goals can be funded by diverting money from the arms companies. Health professionals and their organisations have a responsibility to children to try and curb the ever-expanding arms industry.